The effects of blackcurrant and caffeine combinations on performance and physiology during repeated high-intensity cycling - Paton, C. D.; Morton, L. C.; Bomal, B.; Braakhuis, A. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Blackcurrant juices and extracts containing anthocyanin may provide ergogenic benefits to sports performance. However, there are no studies examining the effects of coingestion of blackcurrant and caffeine. This investigation examined the effects of acute supplementation with a proprietary blackcurrant beverage administered in isolation or in combination with caffeine on repeated high-intensity cycling. Twelve well-trained male cyclists (mean ± SD: age, 39.5 ± 11.4 years; height, 177.9 ± 5.7 cm; weight, 78.2 ± 8.9 kg; and peak oxygen consumption, 4.71 ± 0.61 L/min) completed experimental sessions consisting of repeated (8 × 5 min) maximal intensity efforts. Four experimental treatments were administered in a double-blind, balanced Latin square design: blackcurrant + caffeine, blackcurrant + placebo, caffeine + placebo and placebo + placebo. Differences in power output, heart rate, oxygen consumption, muscle oxygen saturation, rate of perceived exertion, and cognitive function (Stroop) were compared between treatments using two-way repeated-measures analysis of variance and effect size analysis. There were no significant differences (p > .05) in either physiological or cognitive variables with any supplement treatment (blackcurrant + caffeine, blackcurrant + placebo, and caffeine + placebo) relative to placebo + placebo. Moreover, any observed differences were deemed trivial (d < 0.2) in magnitude. However, power output was lower (p < .05) in blackcurrant + placebo compared with blackcurrant + caffeine. A blackcurrant extract beverage administered in isolation or combination with caffeine provided no beneficial effect on cycling performance or physiological measures relative to a placebo control.